Prologue and philosophy. Commentary on “An Attempt at Self-Criticism” - Víctor Berríos Guajardo (HYBRIS: Revista de Filosofía, 2014)
In 1885 Nietzsche, after editorial and philosophical failure of "Thus Spoke Zarathustra", decides to publish your old books intended to stand as a philosopher who has developed his thinking continuously. For these books, write forewords which exposes a vital context for understanding these works, and that context is none other than the disease. It is the disease which has allowed the development of his work, and the prologues are the story of how, despite the disease, has been able to overcome or, in other words, how to overcome the disease is the invention of himself through writing